2020
DOI: 10.2106/jbjs.19.01166
|View full text |Cite
|
Sign up to set email alerts
|

Education Increases Disposal of Unused Opioids After Total Joint Arthroplasty

Abstract: Background: Unused opioid pills are a danger to patients and their loved ones as they may be diverted for abuse or misuse. The purpose of this study was to determine the baseline rate of proper disposal of unused opioids among patients undergoing total joint arthroplasty and to determine how education impacts disposal rates. Methods: In this study, 563 patients undergoing primary total joint arthroplasty (183 patients undergoing total hip arthroplasty, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…In fact, 70%-75% of abusers obtained opioids through methods of diversion and only 5% from drug dealers or strangers [ 46 51 ]. Consistent with our findings, recent studies have demonstrated that prior instruction in safe opioid handling practices was highly associated with returning medications to a pharmacy, and was the factor most strongly associated with returning medications to a clinician [ 52 57 ]. Consequently, it is essential that orthopaedic surgeons, as well as other hospital and community HCPs allocate sufficient time toward educating patients on safe opioid handling practices and the potential danger of opioid diversion.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, 70%-75% of abusers obtained opioids through methods of diversion and only 5% from drug dealers or strangers [ 46 51 ]. Consistent with our findings, recent studies have demonstrated that prior instruction in safe opioid handling practices was highly associated with returning medications to a pharmacy, and was the factor most strongly associated with returning medications to a clinician [ 52 57 ]. Consequently, it is essential that orthopaedic surgeons, as well as other hospital and community HCPs allocate sufficient time toward educating patients on safe opioid handling practices and the potential danger of opioid diversion.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, 70%-75% of abusers obtained opioids through methods of diversion and only 5% from drug dealers or strangers [46][47][48][49][50][51]. Consistent with our findings, recent studies have demonstrated that prior instruction in safe opioid handling practices was highly associated with returning medications to a pharmacy, and was the factor most strongly associated with returning medications to a clinician [52][53][54][55][56][57]. Consequently, it is essential that orthopaedic surgeons, as well as other hospital and community HCPs allocate sufficient time toward educating patients on safe opioid handling practices and the potential danger of opioid diversion.…”
Section: Plos Onesupporting
confidence: 89%
“…International experience would also suggest that the use of perioperative opioids increases the rate of hospital readmission post lower limb arthroplasty and the length of stay in hospital after these procedures [6,7]. Numerous efforts have been made to both understand and mitigate the factors contributing to opioid abuse in the context of lower limb arthroplasty [8,9]. We have demonstrated that the 'on-demand' opioid requirements for bilateral THA patients are significantly reduced with the use of perioperative steroids.…”
Section: Discussionmentioning
confidence: 90%